2019
DOI: 10.1002/smi.2906
|View full text |Cite|
|
Sign up to set email alerts
|

Work‐related stress and cognitive performance among middle‐aged adults: The Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil)

Abstract: Assessing risk factors exposure, such as stress in the workplace during adulthood, may contribute to detecting early signs of cognitive impairment in order to implement effective actions to improve brain health and consequently to decrease cognitive disorders later in life. In this cross-sectional study, we aimed to investigate whether work-related stress is associated with low cognitive performance in middleaged adults from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) andwhether social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…In the article by de Souza‐Talarico et al, 2020, Figure 1 was incorrectly labeled as Figure 2, and Figure 2 was incorrectly labeled as Figure 1. The correct labelling of the Figures is included below.…”
Section: Figurementioning
confidence: 99%
“…In the article by de Souza‐Talarico et al, 2020, Figure 1 was incorrectly labeled as Figure 2, and Figure 2 was incorrectly labeled as Figure 1. The correct labelling of the Figures is included below.…”
Section: Figurementioning
confidence: 99%
“…The difference was divided by the sample standard deviation (SD). Thus, a Z score of—1 represents a cognitive performance that is 1 SD below the mean sample score for each test ( Rawlings et al, 2014 ; Souza-Talarico et al, 2020 ). A composite EF Z score was calculated by averaging the Z scores of the FAB, FAS letters fluency test, Letter-Number Sequencing, Digit span forward and backward, and completed categories from WCST and then standardizing this mean ( Rawlings et al, 2014 ; Paradela et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that hypertensive individuals perform worse in tests that assess executive functions (EF) compared to healthy individuals ( Moraes et al, 2020 , 2019 ). Souza-Talarico et al (2020) also found that work-related stress was associated with lower performance on delayed recall, verbal fluency, and EF tests in middle-aged adults ( Souza-Talarico et al, 2020 ). Therefore, AH and stress can be both independent risk factors for cognitive impairment.…”
Section: Introductionmentioning
confidence: 97%
“…It also causes stress-related disorders such as cardiovascular disease, depression, anxiety, and burnout (de Souza-Talarico et al, 2020).…”
Section: Introductionmentioning
confidence: 99%